2017
DOI: 10.1016/j.jpain.2017.02.438
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spinal GABAB Receptors in Cancer-Induced Bone Pain in Rats

Abstract: Our findings provide, to our knowledge, the first evidence that downregulation of GABABRs contribute to the development and maintenance of CIBP and restored diminished GABABRs attenuate CIBP-induced pain behaviors at least partially by inhibiting the protein kinase/cAMP-response element-binding protein signaling pathway. Therefore, spinal GABABR may become a potential therapeutic target for the management of CIBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…Taken together, these results provided strong evidence that the CaMKII/CREB signaling pathway may be a critical downstream pathway of CXCR4 under BCP situation, indicating that suppressing the activation of CaMKII/CREB signaling pathway may be an alternative therapeutic strategy for the management of BCP. In addition, our recent study also confirmed the role of CREB under BCP condition (Zhou et al, 2017).…”
Section: Camkii and Bone Cancer Painsupporting
confidence: 73%
“…Taken together, these results provided strong evidence that the CaMKII/CREB signaling pathway may be a critical downstream pathway of CXCR4 under BCP situation, indicating that suppressing the activation of CaMKII/CREB signaling pathway may be an alternative therapeutic strategy for the management of BCP. In addition, our recent study also confirmed the role of CREB under BCP condition (Zhou et al, 2017).…”
Section: Camkii and Bone Cancer Painsupporting
confidence: 73%
“…Suspensions of tumor cells (4 × 10 7 cells/mL) in phosphate buffer saline (PBS) were prepared for injection using a hemocytometer. The model of CIBP was performed as described previously [15] , [16] . In brief, the right leg was disinfected after anesthetized with pentobarbital sodium (50 mg/kg, intraperitoneal, i.p.).…”
Section: Methodsmentioning
confidence: 99%
“…The sections were then captured using a fluorescence microscope (DM2500, Leica, Germany). The Iba1-immunolabeled surface areas were measured in laminae I-IV of the spinal cord dorsal horn using Image Pro Plus software as described previously [15] . Quantification of the immunoreactivity was accomplished by calculating the percentages of immunostaining ([positive immunofluorescent surface area]/[total measured picture area] × 100).…”
Section: Methodsmentioning
confidence: 99%
“…For drug administration, intrathecal (i.t.) catheters were implanted using a lumbar approach, as described previously ( Zhou et al, 2017 ). Briefly, animals were anesthetized with intraperitoneal injection (i.p.)…”
Section: Methodsmentioning
confidence: 99%